Pemetaan Usaha Cafe Di Manahan Dengan Menggunakan Metode Naive Bayes Studi Kasus Dinas Perdagangan - Paulus Harsadi; Dwi Remawati; Kriswantoro Budi Satrio (STMIK Sinar Nusantara, 2020)
There are many cafes in Manahan, Surakarta. Café can be found almost in every street and it usually visits teenagers. In several years, businesses café grow rapidly in Manahan. Nowadays there are a lot of teenagers who have a habit of hanging out in the café. The purpose of this study is to build a mapping business café in Manahan using Naïve Bayer Method. It is caused to determine a large variable which has high potential for the surrounding point. It cannot be denied that using Naïve Bayes Method can help people to determine the mapping business café. The result of this study is arranged based on the lowest value which is consisting of micro, small and medium. Keywords: Mapping, Naive Bayes, Application